2021
DOI: 10.1007/s12325-021-01649-2
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Nephrolithiasis and Nephrocalcinosis in Patients with Chronic Hypoparathyroidism: A Retrospective Cohort Study

Abstract: Introduction: Chronic hypoparathyroidism managed with conventional treatment, comprising oral administration of calcium and active vitamin D, has been associated with renal complications, including nephrolithiasis and nephrocalcinosis. Further larger-scale studies are needed to examine these risks. This study

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 25 publications
1
15
1
Order By: Relevance
“…Results from this study strengthen an accumulating body of evidence indicating that patients with chronic hypoparathyroidism treated with conventional therapy are at increased risk for the development and progression of CKD 2,3,6,8,9 . Retrospective claims database studies reported that patients with hypoparathyroidism were at increased risk of developing CKD, nephrolithiasis, nephrocalcinosis and decline in eGFR compared with individuals without hypoparathyroidism 6,8,9 .…”
Section: Discussionsupporting
confidence: 71%
“…Results from this study strengthen an accumulating body of evidence indicating that patients with chronic hypoparathyroidism treated with conventional therapy are at increased risk for the development and progression of CKD 2,3,6,8,9 . Retrospective claims database studies reported that patients with hypoparathyroidism were at increased risk of developing CKD, nephrolithiasis, nephrocalcinosis and decline in eGFR compared with individuals without hypoparathyroidism 6,8,9 .…”
Section: Discussionsupporting
confidence: 71%
“…The assessment of urinary calcium excretion identifies patients at risk of developing kidney stones and/or nephrocalcinosis and decline of renal function. Even if recent studies did not find a clear correlation between kidney stones and hypercalciuria (148), or between urinary biochemical parameters and kidney outcomes (146), patients with HypoPT should be considered at a high risk of developing nephrolithiasis, nephrocalcinosis (149), as well as chronic kidney disease (146), Table 4.…”
Section: Q9 Which Biochemical Parameters Should Be Monitored To Adjus...mentioning
confidence: 99%
“…The theory hypothesized that the pathophysiology is potentially through hypercalciuria. Alternatively, another hypothesis suggests the course of the disease and scarcity of normal physiological effect of parathyroid hormone on renal tubules being a risk factor for nephrocalcinosis and nephrolithiasis in hypoparathyroidism [ 12 ]. Inclusively, the calcium correction in hypoparathyroidism is linked with nephrolithiasis and many other renal complications [ 13 ].…”
Section: Discussionmentioning
confidence: 99%